2010
DOI: 10.1088/0953-2048/23/4/045013
|View full text |Cite
|
Sign up to set email alerts
|

Effective silver-assisted welding of YBCO blocks: mechanical versus electrical properties

Abstract: Superconducting welding of bulk YBCO is a key technology allowing the fabrication of large, complex-shaped pieces for applications such as levitation, bearings or large magnets. Ideally, the electrical and mechanical properties of welds should be comparable to that of the joint grains. In this paper, we have investigated the correlation between the microstructural, mechanical and critical current density performances of melt-textured [001]-tilt YBCO welds fabricated by the silver welding technique. The hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To calculate the value of d c for each film present in the two stacks rather than the modulus of the Burger vector, to first approximation it is possible to consider the spacing between the (001) planes of the different crystal structures. The values of the Poisson's ratios for the grown films are reported in Table 2 [16][17][18][19][20]. By using the measured lattice parameters we have found that for our layer combinations, the critical thickness is less than 10 nm.…”
Section: Theoretical Values For the Residual Stressmentioning
confidence: 99%
“…To calculate the value of d c for each film present in the two stacks rather than the modulus of the Burger vector, to first approximation it is possible to consider the spacing between the (001) planes of the different crystal structures. The values of the Poisson's ratios for the grown films are reported in Table 2 [16][17][18][19][20]. By using the measured lattice parameters we have found that for our layer combinations, the critical thickness is less than 10 nm.…”
Section: Theoretical Values For the Residual Stressmentioning
confidence: 99%